Sustainable supply chain management framework in a higher education laboratory using intuitionistic fuzzy cognitive map - Muhammad Ridwan Andi Purnomo; Adhe Rizky Anugerah; Bella Taradipa Dewipramesti (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: This research aims to develop framework in the sustainable supply chain management (SCM) and to provide causal model of service industry specifically in higher education laboratory. Design/methodology/approach: The concepts of sustainable SCM in higher education laboratory were obtained by in-depth interviews and organized using Delphi method. While to identify the relationship between concepts, intuitionistic fuzzy cognitive map was utilized. Findings: As many as 15 concepts were identified to assess sustainability in the higher education laboratory SCM. These 15 concepts were classified into four categories according to its importance level, and there are two most important concepts: legal requirement and social responsibility. It is recommended for higher education laboratories to constantly obey national and regional government regulations and to satisfy current and prospective employers by providing work-ready graduates. This suggestion is expected to make higher education achieving its sustainability goals. Originality/value: This research is the first to develop a framework for sustainable SCM and to provide a causal model of the service industry especially in the education sector using intuitionistic fuzzy cognitive map.
Keywords: 650; Causal model; intuitionistic fuzzy cognitive map; laboratory; service supply chain; sustainable